Scrambled Features for Breakfast: Concepts of Agile Language Development. - CAZZOLA, WALTER; FAVALLI, LUCA (Communications of the ACM, 2023)
This article proposes the development of agile programming languages intended for specific domains. The authors share their work on creating Tyl, a programming language for enterprise resource planning applications utilizing Scrum as the agile process and Neverlang as the language workbench. Topics include the detailed process of Scrum including sprints, completion of product backlog items, and addressing challenges encountered for development of a domain-specific programming language.